Sharing borders: studies in contemporary Singaporean-Malaysian literature - Quayum, Mohammad Abdul (Singapore National Library Board and Singapore National Arts Council, 2009)
Sharing Borders, Volume 2 in the Writing Asia Series, is the most comprehensive account to date of Singaporean and Malaysian literatures in English. Apart from the assessment of single authors, surveys and special topics, it provides essential background, traces origins and early development, the way significant themes in the life of the two nations have evolved and been articulated, and how succeeding generations of writers – especially in Singapore – show greater freedom and confidence exploiting the possibilities of their language. Each of the two Parts has a substantial Introduction and essays by thirty scholars and practitioners who include some of the most distinguished names in the field.